11x-3(5x-4)=2+6(x+5)

Simple and best practice solution for 11x-3(5x-4)=2+6(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-3(5x-4)=2+6(x+5) equation:


Simplifying
11x + -3(5x + -4) = 2 + 6(x + 5)

Reorder the terms:
11x + -3(-4 + 5x) = 2 + 6(x + 5)
11x + (-4 * -3 + 5x * -3) = 2 + 6(x + 5)
11x + (12 + -15x) = 2 + 6(x + 5)

Reorder the terms:
12 + 11x + -15x = 2 + 6(x + 5)

Combine like terms: 11x + -15x = -4x
12 + -4x = 2 + 6(x + 5)

Reorder the terms:
12 + -4x = 2 + 6(5 + x)
12 + -4x = 2 + (5 * 6 + x * 6)
12 + -4x = 2 + (30 + 6x)

Combine like terms: 2 + 30 = 32
12 + -4x = 32 + 6x

Solving
12 + -4x = 32 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
12 + -4x + -6x = 32 + 6x + -6x

Combine like terms: -4x + -6x = -10x
12 + -10x = 32 + 6x + -6x

Combine like terms: 6x + -6x = 0
12 + -10x = 32 + 0
12 + -10x = 32

Add '-12' to each side of the equation.
12 + -12 + -10x = 32 + -12

Combine like terms: 12 + -12 = 0
0 + -10x = 32 + -12
-10x = 32 + -12

Combine like terms: 32 + -12 = 20
-10x = 20

Divide each side by '-10'.
x = -2

Simplifying
x = -2

See similar equations:

| 2ln(x)-ln(5)=ln(x+10) | | 6(4+c)=5(c-6) | | 4v^2=-21v-5 | | 84=1x+96 | | 26z+9+11+-17z=-16+9 | | 17x-8=7x+2 | | (4/p)+(5/2)=7/p | | 22,45:0,345= | | 2/3*2/5= | | 100=10b+3g+50-.5b-.5g | | (5y-1)(5+y)=0 | | 3(4z-3)-3(2-2z)=6 | | x/9=3/2 | | 10,000^5/4 | | 5m+4*(m-4)= | | 18x^2-59x=-34 | | 5m+4(m-4)= | | 3x+30=24x-120 | | 3-1/2x=-2 | | 7x+x+8-2x+5=45 | | 6y+y+5y= | | 3xa-4xb+5xa-3xb= | | 2(4x-3)=10 | | 9x+237=4x+172 | | 4(y-2)-9=-7(-2y+5)-2y | | 11-w/2=60 | | 4x(5x+7)= | | ax^2+6ax+9a=0 | | -x+15-3x+6=-7x-4x | | (25.12^2)/(4(3.14)) | | -6/7x+17=-61 | | 7/9-5/13 |

Equations solver categories